ANALISIS DALAM PENGELOLAAN PERPAJAKAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TAHUN 2024 DI SDN PORIS PELAWAD 4 KOTA TANGERANG - Virgitrianya; Totok Priyono (Jurnal Ilmu Administrasi Publik, 2026)
The implementation of taxation management in the School Operational Assistance Fund (BOS) is an important part of creating transparent and accountable financial management in education. However, in practice, elementary schools still face challenges in optimally implementing their tax obligations. This study aimed to analyze the implementation of tax management in the 2024 BOS Fund at SDN Poris Pelawad 4 in Tangerang City, focusing on the policy implementation process, the obstacles faced, and efforts to overcome these obstacles. This study used a descriptive qualitative approach with George C. Edward III's policy implementation theory, which includes the dimensions of communication, resources, disposition, and bureaucratic structure. Data collection techniques were carried out through observation, in-depth interviews, documentation, and triangulation with key informants, namely the school principal, school committee, treasurer, and school operator. The results of the study indicated that the implementation of BOS Fund tax management has been carried out in accordance with regulations but has not been optimal. Based on Edward III's theory, obstacles were found in the aspects of ineffective communication, limited human resources who did not fully understand the technical aspects of taxation, resulting in administrative errors, the disposition of implementers who did not fully understand their tax duties, and a weak bureaucratic structure in terms of internal coordination and supervision. Improvement efforts were carried out through technical training from the Education Office, internal school coordination, encouragement of self-training, the development of a tax guidebook, and the involvement of the committee in regular reporting. Keywords Implementation, Policy Implementation, Taxation, BOS Founds, Edward III